BEHIND THE SCENES OF AN NBA PROGRAM. STAFF MANAGEMENT, PRACTICE AND GAME PLANNING. THE ROLE OF ANALYTICS - Finch, Chris (Sport- és Egészségtudományi füzetek, 2025)
Culture and Sport now is a very popular term, oftentimes, maybe even overused. What does the culture mean? It’s just about the things that you choose to emphasize. Well that you choose to enforce to your players your staff and your team. So whatever those things are, you have to figure out what’s most important to you. A head coach’ job is less about X’s and O’s, and a lot more about leadership. The NBA has a big staff of 15 people, includ-ing four senior coaches, four player development coaches, and a support staff. The head of the staff is responsible for skill acquisition, skill development, and preparing individ-ual programs for players. The support staff includes three video coordinators, who help younger players learn the league terminology and coaches’ tendencies. The analytics department, consisting of five or six people, is responsible for game planning and interpreting data. The analytics per-son is embedded in the staff for game planning purposes and a newly hired staff member prepares a game plan and reviews it after each game.